Analisis Sentimen Komentar Pengunjung Terhadap Tempat Wisata Danau Weekuri Menggunakan Metode Naive Bayes Classifier Dan K-Nearest Neighbor - Gergorius Kopong Pati; Elfira Umar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Trip Advisor is the largest travel site in the world that helps tourists in planning and booking travel. One of the recommended attractions on the TripAdvisor website is the Crystal Cave, which is located in Kupang City. Human habit in posting tourist attractions visited is a common thing to present human responses to one of the tourist attractions. Usually there are certain parties who want to know the sentiments and responses to one of the tourist attractions. Therefore, this study will conduct a sentiment analysis of one of the tourist attractions in the city of Kupang is the Crystal Cave. The analysis was carried out by classifying people's sentiments. The calcification method used in this study is Navie Bayes Classifier and K-Nearest Neighbor. From these two methods a comparison will be done to find out the level of accuracy. Sentiment classification consists of positive and negative. The purpose of this study is to provide information about the quality of one of the tourist attractions in the city of Kupang by using sentiment from visitors and determine the level of accuracy of the comparison of the two methods tested. The test results will be tested on the Rapidminer tool showing the level of accuracy of testing both methods.